Pengaruh Pengawasan Dan Disiplin Kerja Terhadap Kinerja Pegawai Dengan Keterlibatan Pegawai Sebagai Variabel Intervening Pada Pengadilan Tinggi Padang - Tiansy Aurora Iskandar; Desi Pertama Sari; Silvia Sari (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the effect of supervision and work discipline on employee performance with employee engagement as an intervening variable using primary data obtained by distributing questionnaires to 48 employees as respondents, namely at the Padang High Court. In this study, a structural equation analysis tool (SEM) using Partial Lears Square (PLS) was used. The results of the study indicate that supervision has a negative and insignificant effect on employee engagement, work discipline has a positive and significant effect on employee engagement, supervision has a negative and insignificant effect on employee performance, work discipline has a negative and insignificant effect on employee performance, employee engagement has a positive and significant effect on employee performance, employee engagement is unable to mediate the effect of supervision through employee performance, work discipline is able to mediate the effect of work discipline on employee performance.